The influence of pH and temperature changes on the adsorption behavior of organophilic clays used in the stabilization/solidification of hazardous wastes. Issue 2 (1st March 2002) - Bishop, Paul L; Uribe, Alberto; Pinto, Neville G
Abstract : The effect of temperature, pH, and Na + /Ca 2+ concentration on the adsorptive behavior of organophilic clay used in the solidification/stabilization of hazardous wastes was addressed. The organophilic clay used was montmorillonite type clay modified by cation exchange with a mixed tallow amine as the sorbent. The contaminants used in this work were phenol, 2-chlorophenol, aniline, and chlorobenzene. 2-Butanone (also known as methyl ethyl ketone, MEK) was initially studied, but preliminary work showed that the organophilic clay poorly sorbed it and it was not studied further. A group of isothermal tests were performed to clarify specific sorption behaviors due to temperature effects, high pH, and concentration of the cations Na + and Ca 2+ . The adsorption capacity of the organophilic clay decreased as follows: chlorobenzene > 2-chlorophenol > phenol > aniline. Desorption in high pH environments was seen for phenol and 2-chlorophenol. Changes in temperature, rise in the pH, or increases in Na + /Ca 2+ concentrations had no effect on the adsorption of either aniline or chlorobenzene.